HUBUNGAN POLA ASUH ORANG TUA DENGAN TINGKAT KECEMASAN ANAK PADA ADAPTASI SEKOLAH DI SEKOLAH DASAR NEGERI CILANDAK BARAT 04 PAGI JAKARTA SELATAN - Duma Lumban Tobing (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2019)
Inability to adapt to the new environment at the beginning of the school children can cause anxiety response. This study aims to determine the relationship between parenting parents to a child's anxiety levels during elementary school adaptation with total sample 54 respondents . The sample was parents who have children who were new students at SDN 04 Morning Cilandak Barat, South Jakarta in the academic year 2013-2014. This study used a descriptive quantitative method with a